Biomechanics of cycling (Springer, 2014)
Bicycles have been a common device to enhance physical fitness level in gyms and training centers along with solid use in competitive sport. For that reason, biomechanics of cycling has grown as a research field with many publications addressing different perspective of the interaction between the cyclist and his bicycle. The most common end point of research on biomechanics of cycling is optimization of performance and reduction of injury risk. One goal of this book is to meet the growing need for a comprehensive presentation of contemporary knowledge on biomechanics of cycling which will positively influence the activity of cycling in a global fashion. In order to accomplish this purpose, ten chapters are presented with focus on varying methods for biomechanical analysis of cycling motion. The introduction section provides an overview of the main methods for assessment of cycling motion, including motion analysis, pedal force measurements, muscle activation, anthropometry and joint kinetics. These methods are discussed in depth in individual chapters followed by chapters on characteristics of bicycles and potential perspectives to improve their configuration in order to improve performance of cyclists and reduce their overuse injury risk. Moreover, a preliminary method to train technique in cyclists is shown. A final chapter provides authors perspective on the upcoming technology that should be effective in helping training of cyclists. (Abstract by Springer)